2017
DOI: 10.2135/cropsci2016.06.0542
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐Induced Leaf Senescence Associated with Chlorophyll Metabolism in Bentgrass Lines Differing in Heat Tolerance

Abstract: Leaf senescence is characterized by decreased chlorophyll content in leaves. The objectives of this study were to determine whether heat‐induced chlorophyll decline is due to inhibited chlorophyll synthesis or accelerated chlorophyll degradation and to determine whether genetic variations in heat tolerance of bentgrass (Agrostis spp.) species were associated with differential chlorophyll‐enzymatic responses to heat stress. Five turfgrass lines, including two transgenic creeping bentgrass (A. stolonifera L.) li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…Under normal growth conditions, the synthesis and degradation of Chl reach equilibrium and the levels of this molecule remain stable (Ginsburg et al, 1994;Hörtensteiner, 2006;Wang et al, 2018). Conversely, when plants are subject to environmental stress, including heat, the content of Chl decreases, leading to leaf senescence or chlorosis Lim et al, 2007;Allakhverdiev et al, 2008;Rossi et al, 2017). Under heat treatment, the activity of chlorophyllase and Chl-degrading peroxidase dramatically increases, resulting in a serious reduction in Chl levels (Figure 2; Wang et al, 2018).…”
Section: Chlorophyllmentioning
confidence: 99%
“…Under normal growth conditions, the synthesis and degradation of Chl reach equilibrium and the levels of this molecule remain stable (Ginsburg et al, 1994;Hörtensteiner, 2006;Wang et al, 2018). Conversely, when plants are subject to environmental stress, including heat, the content of Chl decreases, leading to leaf senescence or chlorosis Lim et al, 2007;Allakhverdiev et al, 2008;Rossi et al, 2017). Under heat treatment, the activity of chlorophyllase and Chl-degrading peroxidase dramatically increases, resulting in a serious reduction in Chl levels (Figure 2; Wang et al, 2018).…”
Section: Chlorophyllmentioning
confidence: 99%
“…In contrast, chlorophylls undergo turnover or breakdown when the partial or complete dismantling of the photosynthetic machinery occurs in response to environmental stresses, including heat stress. Heat stress symptoms in plants are typically characterized by leaf senescence or chlorosis due to a decline in chlorophyll content [ 2 , 51 , 52 ]. Heat-induced leaf chlorosis has been observed in a variety of plant species, including Arabidopsis [ 4 , 5 , 53 ], Soybean ( Glycine max L.…”
Section: Chlorophyll Breakdown Under Heat Stressmentioning
confidence: 99%
“…It has been reported that regulation of chlorophyll biosynthesis in plants depends on the intensity and type of stress, such as water stress (Dalal & Tripathy ), salt stress (Turan & Tripathy ) and heat stress (Rossi et al . ). Protoporphyrin IX (Proto IX) is one of the end products of the chlorophyll biosynthetic pathway.…”
Section: Introductionmentioning
confidence: 97%